Massive pulmonary embolism – what you may be missing? - Sam, Karun S.; Gogia, Atul; Batra, Tanvi (International Journal of Research in Medical Sciences, 2023)
Our patient is a 68-year-old woman with no known comorbid illnesses, who presented with fever, cough and haemoptysis of 20-days duration. The fever was insidious in onset, intermittent, high grade and was associated with productive cough. There were intermittent episodes of scoughing up of blood-tinged sputum mixed with clots. She was evaluated at another centre and was diagnosed with a pulmonary embolism based on a computed tomographic imaging of the thorax. When she presentation to us, she was hemodynamically stable and her systemic examination was within normal limits. Her computed tomography (CT) scan were reviewed and she was labelled to have an intermediate risk pulmonary embolism. She was initiated on Injection enoxaparin and was simultaneously evaluated for the aetiology of her illness wherein an USG guided supraclavicular lymph node biopsy lead to a diagnosis of extrapulmonary tuberculosis. She was initiated on first line ATT and was discharged on the same. Anticoagulation was continued on discharge. She is currently doing well on follow up. Our objective is to shed light on the association between tuberculosis and pulmonary embolism and to emphasize the need for a thorough evaluation to identify an occult infective focus in patients presenting with venous thromboembolism.